PERANCANGAN EARTH LEAKAGE CIRCUIT BREAKER DENGAN SENSIVITAS 20 MA - Pandung Sarungallo; Adelhard Beni Rehiara (Universitas Ahmad Dahlan, 2008)
Electrics current can flow out to the ground by using a human body. This electric current will be dangerous to the human when it exceed 20mA. A very sensitive earth leakage circuit breaker (ELCB) is needed to anticipate the leaky current but most of ELCB can only be found in the market with sensitivitas 30mA or bigger. This research is succees to design an ELCB with sensitivity 20mA. Characteristic of an ELCB is very influenced by the current transformer characteristic and the relay which are used.